TANGGUNG JAWAB YURIDIS ATAS TINDAKAN INDUK PERUSAHAAN MELAKUKAN PENYERTAAN MODAL KEPADA ANAK PERUSAHAAN (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR: 1038/K/PDT.SUS/2010) - HABIB MUHAMMAD YUSUF SIREGAR (PREMISE LAW JURNAL, 2017)
Since there is no regulation on a group company in Indonesia, it has its own loophole in the law about the liability of holding company in co-financing subsidiaries although Law No. 40/2007 on Corporation states that a holding company and a subsidiary are independent legal entities. The conclusion of the research was that the holding company, Chuan Son Huat Industrial Group (CSH) which co-financed its subsidiary, PT. Cemerlang Selaras Wood Working (PT. CSWW) cannot be categorized as money because it does not meet the elements of the phrase, ‘in amount of money’, and the phrase, ‘based on the agreement’. It is recommended that, in having legal certainty concerning law and liability in group companies, Law No. 40/2007 on Corporation be completed and strengthened. The judges who pronounce judgment on bankruptcy cases and other cases which involve holding companies and subsidiaries should be guided by the principles of legal person, separate legal entity, limited liability, and piercing the corporate veil in order to create legal certainty. Keywords: Group Company, Judicial Liability, Co-financing